2013
DOI: 10.1007/s00259-012-2316-4
|View full text |Cite
|
Sign up to set email alerts
|

PET/MR imaging of the pelvis in the presence of endoprostheses: reducing image artifacts and increasing accuracy through inpainting

Abstract: Endoprostheses cause PET/MR artifacts that exceed the volume occupied by the implants, and bias PET quantification. Artifacts and bias can be corrected by semiautomated inpainting with soft tissue with a single composition prior to MR-AC, thus restoring quantitative activity distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 21 publications
2
47
0
Order By: Relevance
“…Besides the simple algorithm proposed here, complex algorithms for correction of MR-AC image artifacts have been proposed to correct for the MR-AC image artifacts. 34,35,37 A second limitation is that not all image artifacts were corrected in this study. For example, misalignment artifacts (PMA) caused by breathing during MR-AC acquisitions were not compensated for, due to the gradual change of the respiratory phase throughout acquisition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the simple algorithm proposed here, complex algorithms for correction of MR-AC image artifacts have been proposed to correct for the MR-AC image artifacts. 34,35,37 A second limitation is that not all image artifacts were corrected in this study. For example, misalignment artifacts (PMA) caused by breathing during MR-AC acquisitions were not compensated for, due to the gradual change of the respiratory phase throughout acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Misalignment artifacts, on another hand, can be corrected retrospectively using manual coregistrations of the AC maps and the emission data. 19,20 Tissue inversion, however, is more challenging to correct.…”
Section: Discussionmentioning
confidence: 99%
“…Ladefoged et al 105 proposed to semiautomatically segment the signal voids caused by endoprotheses and to fill them with soft-tissue attenuation coefficients. It was demonstrated that the resulting attenuation maps can substantially reduce the underestimation of the SUVs.…”
Section: B1 Void Regions Segmentationmentioning
confidence: 99%
“…It has been reported that the resulting erroneous attenuation map can lead to substantial SUV underestimation by about 50% in the case of hip prosthesis 36 and >100% in dental filling cases. 104 The correction of MR susceptibility artifacts has been explored using the following approaches.…”
Section: B Mr Susceptibility and Respiratory Artifact Reductionmentioning
confidence: 99%
“…The accuracy of MR attenuation correction (AC) is challenged by susceptibility effects caused by dental fillings and metal braces. [4][5][6][7] The effect of a metal implant can be a signal void around the metal filling in the MR images [Figs. 1(a)-1(c)], resulting in the area incorrectly being set to air in the μ-map [ Fig.…”
Section: Introductionmentioning
confidence: 99%